a. 8x + 3y + 16x + 16y =
b. (4a + 6b − 2c) + (9a + 3b + 11c) =
c. (8x2 − 4y2 + 2z2 − 2x + 20y + 9z + 1) + (7x2 + 9y2 − 3z2 + x − y + z − 4) =
d. (5a + 16 − c2 + 2b + 17c) + (4c2 − 2c + 4a − 4 + 11b) =
Respuestas
Respuesta dada por:
1
Respuesta:
Explicación paso a paso:
a. 8x + 3y + 16x + 16y = 24x+19y
----
b. (4a + 6b − 2c) + (9a + 3b + 11c) =13a+9b+9c
----
c. (8x2 − 4y2 + 2z2 − 2x + 20y + 9z + 1) + (7x2 + 9y2 − 3z2 + x − y + z − 4) =
15x²+5y²-z²-x+19y+10z-3
-------
d. (5a + 16 − c2 + 2b + 17c) + (4c2 − 2c + 4a − 4 + 11b) =
9a+12+3c²+13b+15c
----
Preguntas similares
hace 3 años
hace 6 años
hace 8 años
hace 8 años